Characterization of Emissions from Carbon Dioxide Laser Cutting Acrylic Plastics - Munoz, Alejandro; Schmidt, Jacob; Suffet, I H Mel; Tsai, Candace Su-Jung (ACS Chemical Health & Safety., 2023)
Carbon dioxide laser cutters are used to cut and engrave on various types of materials, including metals, wood, and plastics. Although many are equipped with fume extractors for removing airborne substances generated during laser cutting, gases and particulate matter can be released upon opening the lid after completion. This study focused on investigating laser cutting acrylic sheets and associated emissions. Real-time instruments were utilized to monitor both particulate concentrations and size distributions, while the patented Tsai diffusion sampler was used to collect particulate samples on a polycarbonate membrane and transmission electron microscopy (TEM) grid. Identification of released gases consisted of the use of gas sampling with Teflon gas bags followed by analysis using gas chromatography-mass spectrometry (GC-MS). A portable ambient infrared air analyzer was used to quantify the concentrations of the chemicals released by laser cutting activities. The results of the study found that a significant concentration of particulate matter, including nanoplastic particles ranging 15.4-86 nm in particle sizes, and microplastics with agglomerates were released each time the laser cutter lid was opened and were observed to gradually increase in concentration for a period of at least 20 min after the completion of a cut. The GC-MS gaseous samples primarily contained methyl methacrylate at a low level close to the detection limit of the infrared air analyzer.